Field notes contributed by Dennis Henrickson, fall 1996 - Henrickson, Denniset al (1996)
List of birds and locations contributed by Dennis Henrickson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed/flatbed